State of the Art in the Treatment of Congenital Agenesis With Implant-Supported Prosthesis: A Comprehensive Multidisciplinary Management - Oliveira, Gabriela Ezequiel [UNESP]; Pelegrine, Henrique Cassebe Ledo [UNESP]; Barros-Filho, Luiz Antonio B.; Cardoso, Mauricio de Almeida; Ricci, Weber Adad [UNESP]; Barros, Luiz Antonio Borelli [UNESP]; Avila, Erica Dorigatti de [UNESP]; Molon, Rafael Scaf de [UNESP] (Wiley, 2024)
Congenital dental agenesis, particularly in younger adults, can have a profound impact on aesthetics and overall quality of life. The scientific literature offers various management strategies for this condition, with orthodontic movement and implant-supported rehabilitation being central to treatment. However, achieving predictable and successful outcomes necessitates a comprehensive multidisciplinary approach. Such an approach integrates diverse professional perspectives to ensure accurate diagnosis, prognosis, and treatment planning, ultimately aiming to restore dental function and address aesthetic concerns effectively. In this case report, we present the successful rehabilitation of a young patient with congenital agenesis of the mandibular central incisors. The treatment strategy combined oral surgery (extraction of deciduous teeth and autogenous bone graft), orthodontic movement (opening spaces to allow implant installation), periodontics (connective tissue graft), implantology, and prosthetic planning. We detail the specific surgical approaches employed and discuss how their integration contributed to the overall success of the case. This multidisciplinary treatment approach not only restored dental function but also met the patient’s aesthetic expectations and enhanced the patient’s quality of life, highlighting the importance of a coordinated approach in managing complex dental conditions.
Keywords: bone graft; dental agenesis; dental implant; oral rehabilitation; orthodontics